Nursing diagnosis manual : planning, individualizing, and documenting client care - Doenges, Marilynn E., 1922-; Moorhouse, Mary Frances, 1947-; Murr, Alice C., 1946- (Philadelphia : F.A. Davis, 2022)
'This book is designed to aid the student nurse and the practitioner in identifying interventions commonly associated with specific nursing diagnoses as disseminated by NANDA International. These interventions are the activities needed to implement and document care provided to the individual client and can be used in varied settings from acute to community/home care'--
The nursing process. The foundation of quality client care -- The language of nursing. NANDA, NIC, NOC, and other standardized nursing languages -- The assessment process. Developing the client database -- Developing and documenting the plan of care -- Nursing diagnoses in alphabetical order -- Health conditions and client concerns with associated nursing diagnoses.
Description based on print version record.
Nurse's pocket minder affixed to back cover.
Includes bibliographical references and index.
WorldCat record variable field(s) change: 050, 082, 650
Keywords: Nursing diagnosis; Nursing care plans; Nursing records; Nursing Diagnosis; Patient Care Planning; Nursing Records; Diagnostics infirmiers; Plans de soins; Soins infirmiers -- Feuilles de soins; Nursing diagnosis